Successful Treatment of Pearly Penile Papules with Carbon Dioxide Laser Resurfacing After Local Anesthesia in an Adolescent Patient. Issue 3 (29th December 2014) - Krakowski, Andrew C.; Feldstein, Stephanie; Shumaker, Peter R.
Abstract Pearly penile papules (PPP) can cause significant psychological morbidity. Herein we report the successful use of a macrofractionated carbon dioxide laser at full‐field ablative density settings for the treatment of PPP in a 17‐year‐old boy using local anesthetic alone. Our experience leads us to believe that PPP can be successfully treated in the pediatric and adolescent populations using this novel and relatively noninvasive technique.